1909 N.J. Laws 179-80, ch. 113, § 1. - (:unkn) unknown (General Publisher, 1909)
Any person who shall have in his or her possession any dynamite, nitro-glycerine, guncotton or other explosive of any nature whatsoever, with intent to injure any person or persons or with intent to unlawfully injure any property, with, by, or by any use of such dynamite, nitro-glycerine, guncotton or other explosive of any nature whatsoever, shall be guilty of a misdemeanor and punished by imprisonment in the State prison for not less than one year, nor more than five years.
--
Keywords: USE OF EXPLOSIVES WHILE COMMITTING A CRIME